Superior lithium storage properties of β-FeOOH - Yu, Linghui (2015)
Several crystal forms of FeOOH are recently reported to be highly promising for lithium storage due to their high capacity, low cost, and environmental friendliness. In particular, β-FeOOH has shown a capacity of ≈1000 mAh g−1, which is comparable to other promising iron-based anodes, such as Fe2O3 and Fe3O4. However, its storage mechanisms are unclear and the potential for further improvement remains unexplored. Here, it is shown that this material can have a very high reversible capacity of ≈1400 mAh g−1, which is 20%–40% higher than Fe2O3 and Fe3O4. Such a high capacity is delivered from a series of reactions including intercalation and conversion reactions, formation/deformation of solid-state electrolyte interface layers and interfacial storage. The mechanisms are studied by a combination of electrochemical and X-ray absorption near edge spectroscopic approaches. Moreover, very long cycling performance, that is, after even more than 3000 cycles the material still has a significant capacity of more than 800 mAh g−1, is obtained by a simple electrode design involving introducing a rigid support into porous electrodes. Such long cycling performance is for the first time achieved for high-capacity materials based on conversion reactions.